Effects of Curcumin in Combination with Doxorubicin in Human Colorectal Cancer Cell Line - Rostamzadeh Khameneh, Zakieh; Mohammadian, Mahshid; Rasouli, Mohammad Aziz; Moradi, Zhino; Ahmadi, Zohre; Akbarzadeh Khiyavi, Azim (Asian Pacific Journal of Cancer Biology, 2019)
Background: Colorectal cancer (CRC) is one of the main cause of cancer related death worldwide. New therapeutic strategies are required for CRC. Anthracycline drugs such as doxorubicin (DOX) remain one of the most active wide-spectrum and cost-effective drugs in cancer therapy. However, colorectal cancer (CRC) cells are inherently resistant to anthracyclines. Curcumin, the active component and yellow pigment, has been considered as anti-cancer agents with anti-proliferation, anti-invasion, and anti-angiogenesis properties. Previous data show that curcumin may played main role as therapeutic agent for CRC. We aimed to assess the possible sensitizing effects of curcumin in HCT-116 CRC cells treated with DOX. Methods: HCT-116 cells were treated with different doses of curcumin and DOX in increasing concentrations and cytotoxicity were evaluated after 48 h by Water Soluble Tetrazolium Salts(WST-1) method. In double combination treatments (48 h), the mentioned concentration were utilized; D ( Curcumin; 20 μM;DOX;5μM) C (Curcumin; 10 μM;DOX ;2.5μM ), B (Curcumin; 5 μM;DOX;1μM) and A (Curcumin; 2.5 μM;DOX;0.5μM). Results: HCT-116 cells treatments with various concentrations of single agents (DOX and curcumin) decreased the cellular viability in a dose-dependent pattern. Here, we show that treatment of HCT-116 CRC cells with curcumin increases the efficacy of DOX-induced death in HCT-116 cells. Curcumin treatments also results in higher cytotoxicity of DOX and the cell death percent in compared to higher doses in single treatments. Conclusion: It could be concluded that curcumin could acts as chemosensitiser towards the DOX therapy. So it might be used as adjuvant therapy to enhance DOX sensitivity in CRC cells.